The sociology of military science prospects for postinstitutional military design - Paparone, Chris (Bloomsbury Academic, 2013)
This groundbreaking work challenges modernist military science and explores how a more open design epistemology is becoming an attractive alternative to a military staff culture rooted in a monistic scientific paradigm. The author offers fresh sociological avenues to become more institutionally reflexive -- to offer a variety of design frames of reference, beyond those typified by modern military doctrine. Modernist military knowledge has been institutionalized to the point that blinds militaries to alternative designs organizationally and in their interventions. This book seeks to reconstruct strategy and operations in "designing ways" and develops theories of action through multifaceted contextualizations and recontextualizations of situations, showing that military design does not have to rely on set rational-analytic decision-making schemes, but on seeking alternative meanings in- and on-action